2020
DOI: 10.3390/ijerph17186716
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Knowledge, Attitudes and Behaviours among Undergraduate Students in China—Implications for Sex Education

Abstract: Background: Despite rapid modernization and improving gender equity in China in recent decades, traditional values prevail in many areas of life, including sexual behavior. This study aimed to explore gender differences in sexual knowledge, sexual attitudes and sexual behaviors, as well as preferences for sex education among undergraduates in China. Methods: A cross-sectional study surveyed 5965 undergraduates (62.8% females), aged 15 to 24 years from nine universities in Zhejiang, Henan and Yunnan provinces, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 44 publications
6
46
0
Order By: Relevance
“…According to an anonymous survey conducted by Sung et al [ 7 ] among college students in 18 Chinese provinces, a greater proportion of men than of women had engaged in sexual behavior, and more than half of college students who had engaged in sexual activity had not employed appropriate protective measures. Lyu et al [ 8 ] and Chang et al [ 9 ] reported, respectively, that 18.7% and 16% of Chinese college students had previous sex experience, indicating an annually increasing trend.…”
Section: Introductionmentioning
confidence: 99%
“…According to an anonymous survey conducted by Sung et al [ 7 ] among college students in 18 Chinese provinces, a greater proportion of men than of women had engaged in sexual behavior, and more than half of college students who had engaged in sexual activity had not employed appropriate protective measures. Lyu et al [ 8 ] and Chang et al [ 9 ] reported, respectively, that 18.7% and 16% of Chinese college students had previous sex experience, indicating an annually increasing trend.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous studies on “knowledge, attitude and behavior” and behavioral characteristics, college students were sexually active, and a low rate of condom use, multiple sexual partners, casual sexual behavior, and a low awareness of sexual safety were the risk factors for HIV infection [ 10 , 12 , 13 ]. The time of the first sexual act among college students was getting earlier [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of sexual education must not be neglected since teenagers must be informed that sexual-related characteristics and sexually active life are influenced by a lot of factors. Studies [ 12 , 13 , 14 ] have proved that early menarche is related to a high body mass index, diets, poor nutrition, and low physical activity; thus, explaining these risks could increase the quality of life among teenagers. Additionally, early sexual contact is related to a high risk of pregnancy and birth, dropping out of school, and poor socio-economic outcomes and health.…”
Section: Introductionmentioning
confidence: 99%